2008
DOI: 10.1002/num.20348
|View full text |Cite
|
Sign up to set email alerts
|

Finding the one‐loop soliton solution of the short‐pulse equation by means of the homotopy analysis method

Abstract: This version is available at https://strathprints.strath.ac.uk/15055/ Strathprints is designed to allow users to access the research output of the University of Strathclyde. Unless otherwise explicitly stated on the manuscript, Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Please check the manuscript for details of any other licences that may have been applied. You may not engage in further distribution of the material for any pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…It was then shown that breather solition solutions of the SP equation can be generated from those of the SG equation [48]. Another interesting outcome of this SG formulation is that wide range of multi-valued, exotic solutions such as loop solutions can be regarded as the solutions of the SP equation; see, for example, [34,42,32,18,22]. From the theoretical aspects as the partial differential equation (PDE), the global well-posedness of the SP equation (and the SG equation) was discussed by Pelinovsky-Sakovich [43], whereas the local well-posedness was already proved by Schäfer-Wayne [50].…”
mentioning
confidence: 99%
“…It was then shown that breather solition solutions of the SP equation can be generated from those of the SG equation [48]. Another interesting outcome of this SG formulation is that wide range of multi-valued, exotic solutions such as loop solutions can be regarded as the solutions of the SP equation; see, for example, [34,42,32,18,22]. From the theoretical aspects as the partial differential equation (PDE), the global well-posedness of the SP equation (and the SG equation) was discussed by Pelinovsky-Sakovich [43], whereas the local well-posedness was already proved by Schäfer-Wayne [50].…”
mentioning
confidence: 99%
“…In [26] we attempted to formulate the HAM in order to find an analytic approximation to this exact solution. The formulation involved the introduction of a new independent variable as was done in [27] for the short-pulse equation; the resulting equation, corresponding to (4.2), involved higher-order nonlinearities. We found that the approximate solution did not agree well with the exact solution.…”
Section: Discussionmentioning
confidence: 99%